Utilizing Seesaw Application to Lift Students’ Speaking Proficiency in Senior High School - Febby Dwi Cahyani; Dian Fadhilawati; Miza Rahmatika Aini; Hesty Puspita sari (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2024)
In this quantitative study, the researchers assessed the impact of the Seesaw application on eleventh-grade students’ speaking proficiency by focusing on explaining natural phenomena. The researchers utilized pre-experimental research, especially one-group pre- and post-test designs. The research data was gathered through validated pre-tests and post-tests. The statistical analysis encompassed paired sample T-tests with SPSS 25. The result revealed that the students' average speaking score increased significantly from 68.40 to 85.20. The sig 2 tailed was less than 0.05. The results offer compelling support for the integration of Seesaw by English educators, highlighting the potential for enhanced learning outcomes and increased student engagement. Future researchers should delve into comparative studies, scrutinizing the Seesaw application against other digital interactive platforms, including Busuu, ELSA, Cake, Beelinguapp, and similar tools.